2018
DOI: 10.1523/jneurosci.2935-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Association of mGluR-Dependent LTD of Excitatory Synapses with Endocannabinoid-Dependent LTD of Inhibitory Synapses Leads to EPSP to Spike Potentiation in CA1 Pyramidal Neurons

Abstract: The input-output relationships in neural circuits are determined not only by synaptic efficacy but also by neuronal excitability. Activitydependent alterations of synaptic efficacy have been extensively investigated, but relatively less is known about how the neuronal output is modulated when synaptic efficacy changes are associated with neuronal excitability changes. In this study, we demonstrate that paired pulses of low-frequency stimulation (PP-LFS) induced metabotropic glutamate receptor (mGluR)-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…3 f). These results indicate that mGluR5-mediated LTD is robust to AβO [ 102 ] and is independent of mGluR5-mediated PLCβ-dependent eCB mobilization, which is consistent with previous studies [ 103 , 104 ]. Therefore, it is crucial to target more specific downstream pathways of mGluR5 to fully understand the effect of AβO on mGluR5.…”
Section: Discussionsupporting
confidence: 93%
“…3 f). These results indicate that mGluR5-mediated LTD is robust to AβO [ 102 ] and is independent of mGluR5-mediated PLCβ-dependent eCB mobilization, which is consistent with previous studies [ 103 , 104 ]. Therefore, it is crucial to target more specific downstream pathways of mGluR5 to fully understand the effect of AβO on mGluR5.…”
Section: Discussionsupporting
confidence: 93%
“…This LTD of inhibitory transmission (i-LTD) then facilitates the release of glutamate at CA3–CA1 synapses promoting a local LTP. This eCB-mediated metaplasticity can be induced with various cell conditioning paradigms, and most notably subthreshold stimulations (HFS, LFS, TBS or ITDP; Chevaleyre and Castillo, 2003 , 2004 ; Zhu and Lovinger, 2007 ; Lin et al, 2011 ; Pan et al, 2011 ; Xu et al, 2012 ; Basu et al, 2013 ; Orr et al, 2014 ; Monory et al, 2015 ; Silva-Cruz et al, 2017 ; Kim et al, 2019 ). (D) Heterosynaptic eCB-LTP involving astrocytes at CA3–CA1 synapses.…”
Section: Ecb-mediated Synaptic Potentiationmentioning
confidence: 99%
“…long-lasting neural changes induced by activity at a given time, and that modulate subsequently induced plasticity (Abraham, 2008 ), orchestrated by eCBs. This i-LTD is finely tuned by the parallel activation of CB 1 R on GABAergic or glutamatergic cells (Monory et al, 2015 ) and is also accompanied by changes in excitability enhancing the spiking probability in response to a given EPSP, i.e ., EPSP-to-spike potentiation (Chevaleyre and Castillo, 2003 ; Orr et al, 2014 ; Kim et al, 2019 ), and by structural changes (Monory et al, 2015 ; Hu et al, 2019 ) both eCB-mediated. Interestingly, a circuit-based synaptic learning rule, consisting of paired stimulation of the perforant path and Schaffer collaterals, induced an input-timing-dependent heterosynaptic LTP at CA3-CA1 but not at cortical-CA1 synapses (Xu et al, 2012 ; Basu et al, 2013 ).…”
Section: Ecb-mediated Synaptic Potentiationmentioning
confidence: 99%
“…9 It has been shown that more than 50% of rats have neuronal necrosis in the hippocampal CA1 region one month after the establishment of rat models of SES. 10 There is no doubt that CAS can lead to CI, but the mechanism of brain injury caused by CAS is not clear.…”
Section: Introductionmentioning
confidence: 99%